Bacterial neuraminidase facilitates mucosal infection by participating in biofilm production - Grace Soong; Amanda Muir; Marisa I. Gomez; Jonathan Waks; Bharat Reddy; Paul Planet; Pradeep K. Singh; Yukihiro Kanetko; Matthew C. Wolfgang; Yu-Shan Hsiao; Liang Tong; Alice Prince (The Journal of Clinical Investigation, 2006)
Many respiratory pathogens, including Hemophilus influenzae, Streptococcus pneumoniae, and Pseudomonas aeruginosa, express neuraminidases that can cleave α2,3-linked sialic acids from glycoconjugates. As mucosal surfaces are heavily sialylated, neuraminidases have been thought to modify epithelial cells by exposing potential bacterial receptors. However, in contrast to neuraminidase produced by the influenza virus, a role for bacterial neuraminidase in pathogenesis has not yet been clearly established. We constructed a mutant of P. aeruginosa PAO1 by deleting the PA2794 neuraminidase locus (Δ2794) and tested its virulence and immunostimulatory capabilities in a mouse model of infection. Although fully virulent when introduced i.p., the Δ2794 mutant was unable to establish respiratory infection by i.n. inoculation. The inability to colonize the respiratory tract correlated with diminished production of biofilm, as assessed by scanning electron microscopy and in vitro assays. The importance of neuraminidase in biofilm production was further demonstrated by showing that viral neuraminidase inhibitors in clinical use blocked P. aeruginosa biofilm production in vitro as well. The P. aeruginosa neuraminidase has a key role in the initial stages of pulmonary infection by targeting bacterial glycoconjugates and contributing to the formation of biofilm. Inhibiting bacterial neuraminidases could provide a novel mechanism to prevent bacterial pneumonia.